Interaksi Sosial Siswa Berprestasi dan Implikasinya dalam Layanan Bimbingan dan Konseling - Wulandari, Ratna Juwita; Syukur, Yarmis (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2016)
Social interaction is the relationship between individuals and other individuals and with groups that influence each other. Ideally in social interaction there will be cooperation, compromise, emotional control and immediate conflict resolution, but the phenomenon in the field is found by students who are less able to interact with others, close themselves and not have close friends. Therefore, this study aims to describe the social interactions of high achieving students: (1) forms of cooperation, (2) forms of competition, (3) forms of conflict, and (4) forms of accommodation, at Padang State High School 3. This type of research is quantitative with a descriptive approach. The study population amounted to 180 people and samples were taken using purposive random sampling technique. The number of samples is 80 students. The data collection tool used is a questionnaire with a Likert scale. Data were analyzed using percentage techniques. The research findings show that: (1) the form of collaboration is in the good category (37.5%), (2) the form of competition is in the good category (38.8%), (3) the form of conflict is in the good category (42.5%), (4) the form of accommodation is in the fairly good category (36.3%), and in general the social interaction of high achieving students in Padang 3 Public High School is in the good category (42.5%).